Film cooling of a flat plate by one row of inclined holes located in craters at external flow acceleration - Халатов, Артем Артемович; Борисов, Игорь Иванович; Дашевский, Юрий Яковлевич; Коваленко, Александр Сергеевич; Шевцов, Сергей Владимирович (Eastern-European Journal of Enterprise Technologies, 2013)
The results are given of the film cooling experimental study on the flat plate with one array of inclined (α = 300) cylindrical holes in the craters. This data was obtained at 5 < x/d < 30. The relative spanwise pitch of holes t/d was 3.0, while the relative crater depth h/d was 0.8. The film injection parameter was ranged from 0.5 to 2.5. It was shown that laterally averaged film cooling efficiency with holes in craters exceeds the efficiency of the traditional scheme of inclined cylindrical holes. This excess is from 1.5 to 2 times on the initial region, while from 1.1 to 1.3 times beyond this area. Compared to the one-array configuration without craters the investigated film cooling scheme provides more uniform film coverage over the cooled surface. The flow acceleration in the range of 0,5·10-6 < К < 3,5·10-6 for the one array of holes reduces the film cooling efficiency up to 10% depending on the non-dimentional flow velocity. As a result of the experimental data summarizing, the power correlation was obtained describing the lateral averaged film cooling efficiency as a function of the relative main flow velocity for the zero pressure gradient and accelerating flow conditions.